Moving people : sustainable transport development - Cox, Peter, 1964- (Zed ; UCT Press ; Distributed in the USA by Palgrave Macmillan, 2010)
The local and global environmental impacts of transport are more apparent than ever before. Moving People provides an attention-grabbing introduction to the problems of transport and the development of sustainable alternatives, focusing on the often misunderstood issue of personal mobility, as opposed to freight. Re-assessing the value and importance of non-motorized transport the author raises questions about mobility in the face of climate change and energy security, particularly for the developing world. Featuring original case studies from across the globe, this book is essential for anyon.